Strategi Pemasaran Pada UMKM Kawa Daun Celup Putry Bunga Tabek Patah Kecamatan Salimpaung - KHAIRUL MARLIN; Yusratul Rizki; Khairulis Shobirin (Jurnal Manajemen Bisnis Syariah, 2022)
Putry Bunga has produced various products and has carried out promotions but has not achieved steady sales every month. Therefore, the authors conducted a study with the aim of knowing how the marketing strategy implemented by Kawa Daun Celup Putry Bunga SMEs was seen from the 4 P marketing mix indicators (product, price, place and promotion). This type of research is a field research (field research) with a qualitative descriptive method. Data collection techniques were carried out by means of interviews and supported by documents in implementing the marketing strategy used by Kawa Daun Celup Putry Bunga SMEs. The author collects data by interviewing owners and employees. The results showed that Kawa Daun Celup Putry Bunga SMEs have implemented a marketing strategy using the 4P marketing mix indicators, namely in terms of product, price, promotion, and place. In addition, in implementing the marketing strategy, there are several obstacles faced by the Kawa Daun Celup Putry Bunga UMKM, namely the difficulty of maintaining the availability of raw materials and business competition.